Blood Pressure is Associated With Cerebral Blood Flow Alterations in Patients With T2DM as Revealed by Perfusion Functional MRI. Issue 48 (December 2015) - Xia, Wenqing; Rao, Hengyi; Spaeth, Andrea M.; Huang, Rong; Tian, Sai; Cai, Rongrong; Sun, Jie; Wang, Shaohua
Abstract : Abstract: Type 2 diabetes mellitus (T2DM) and hypertension are both associated with cognitive impairment and brain function abnormalities. We investigated whether abnormal cerebral blood flow (CBF) patterns exists in T2DM patients and possible relationships between aberrant CBF and cognitive performance. Furthermore, we examined the influence of hypertension on CBF alterations in T2DM patients. T2DM patients (n = 38) and non-T2DM subjects (n = 40) were recruited from clinics, hospitals, and normal community health screenings. Cerebral blood flow images were collected and analyzed using arterial spin labeling perfusion functional magnetic resonance imaging (fMRI). Regions with major CBF differences between T2DM patients and non-T2DM controls were detected via 1-way ANOVA. The interaction effects between hypertension and T2DM for CBF alterations were also examined. Correlation analyses illustrated the association between CBF values and cognitive performance and between CBF and blood pressure. Compared with non-T2DM controls, T2DM patients exhibited decreased CBF, primarily in the visual area and the default mode network (DMN); decreased CBF in these regions was correlated with cognitive performance. There was a significant interaction effect between hypertension and diabetes for CBF in the precuneus and the middle occipital gyrus. Additionally, blood pressure correlated negatively with CBF in T2DM patients. T2DM patients exhibited reduced CBF in the visual area and DMN. Hypertension may facilitate a CBF decrease in the setting of diabetes. T2DM patients may benefit from blood pressure control to maintain their brain perfusion through CBF preservation. Abstract : Supplemental Digital Content is available in the text